2015
DOI: 10.5152/iao.2015.927
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tone Burst, Click and Chirp Stimulation in Vestibular Evoked Myogenic Potential Testing in Healthy People

Abstract: OBJECTIVE: Vestibular evoked myogenic potential (VEMP) is a clinical test used in the diagnosis of vestibular diseases. VEMP uses several stimulants to stimulate the vestibular system and measure myogenic potentials. The aim of this study was to compare the effects of tone burst, click, and chirp stimulation in VEMP on the latency and amplitude of myogenic potentials. MATERIALS and METHODS:We compared the results of 78 ears from 39 volunteers. We measured the sternocleidomastoid muscle potential of each ear fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 8 publications
5
28
1
Order By: Relevance
“…Although earlier studies have compared P1N1 amplitudes of the cVEMPs across single or two frequencies, 8,14,15 the present study is the initial one to compare cVEMPs over four octaves as often suggested in the literature. 16,17,18 Though the findings of the present study were consistent with the study by Özgür et al 26 and Ocal et al 8 it rejected the claim by some other studies. 14,15,24 Wang et al 24 published the first report of CE-chirp eliciting a significantly greater amplitude than 500 Hz tone bursts.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…Although earlier studies have compared P1N1 amplitudes of the cVEMPs across single or two frequencies, 8,14,15 the present study is the initial one to compare cVEMPs over four octaves as often suggested in the literature. 16,17,18 Though the findings of the present study were consistent with the study by Özgür et al 26 and Ocal et al 8 it rejected the claim by some other studies. 14,15,24 Wang et al 24 published the first report of CE-chirp eliciting a significantly greater amplitude than 500 Hz tone bursts.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…8,14,15,24 However, the amplitude of NB CE-chirp evoked VEMPs remain equivocal as several researchers have reported significantly higher amplitude responses than tone bursts 14,15,24 while others have rejected the claim. 8,26 Therefore, in the present study, we attempted to compare the effects of NB CE-chirps and tone bursts on cVEMPs at four different octave frequencies in younger adults.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 17 , 18 , 19 Besides, lower amplitude values were reported in other studies. 14 , 16 , 20 Moreover, a study indicated that there was no significant difference between tone burst and CHIRP stimulus results. 15 In the current study, the cVEMP response rate with CHIRP stimulus was higher than as was in the previous studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…The earlier studies have used chirps of different bands-200-10,000Hz by Wang et al (6); 500-4000Hz by Özgür et al (7) and 250-1000Hz by Walther et al (8). All these studies compared the c-VEMP responses of chirp with clicks and 500 Hz tone bursts.…”
Section: Tablementioning
confidence: 99%